2007
DOI: 10.1165/rcmb.2006-0372tr
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Lymphangioleiomyomatosis

Abstract: Lymphangioleiomyomatosis (LAM) is a rare progressive cystic lung disease affecting young women. The pivotal observation that LAM occurs both spontaneously and as part of the tuberous sclerosis complex (TSC) led to the hypothesis that these disorders share common genetic and pathogenetic mechanisms. In this review we describe the evolution of our understanding of the molecular and cellular basis of LAM and TSC, beginning with the discovery of the TSC1 and TSC2 genes and the demonstration of their involvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 126 publications
5
80
2
Order By: Relevance
“…The median serum VEGF-D level was elevated in S-LAM subjects without AMLs (1,142 [IQR 659-1,912] pg/mL) and not signifi cantly different from S-LAM subjects with AMLs (1,191 [IQR 878-2,243] pg/mL). There was a trend toward greater VEGF-D elevation in subjects with S-LAM with a history of chylous effusions compared with those without this disease manifestation, but the difference did not reach statistical signifi cance (1,855 [IQR 917-3,014] pg/mL vs 1,142 [IQR 691-1,885] pg/mL, P 5 .086).…”
Section: Serum Vegf-d Levels In Relationship To Disease Featuresmentioning
confidence: 91%
See 1 more Smart Citation
“…The median serum VEGF-D level was elevated in S-LAM subjects without AMLs (1,142 [IQR 659-1,912] pg/mL) and not signifi cantly different from S-LAM subjects with AMLs (1,191 [IQR 878-2,243] pg/mL). There was a trend toward greater VEGF-D elevation in subjects with S-LAM with a history of chylous effusions compared with those without this disease manifestation, but the difference did not reach statistical signifi cance (1,855 [IQR 917-3,014] pg/mL vs 1,142 [IQR 691-1,885] pg/mL, P 5 .086).…”
Section: Serum Vegf-d Levels In Relationship To Disease Featuresmentioning
confidence: 91%
“…Median serum VEGF-D levels were elevated in S-LAM compared with healthy volunteers (1,175 [IQR 780-2,013] pg/mL vs 309 [IQR 211-433] pg/mL, P , .001) ( Fig 4 ). Furthermore, serum VEGF-D levels were normal in emphysema, PLCH, Sjögren with cystic lung disease, and BHD.…”
Section: Determination Of Overall Test Performancementioning
confidence: 93%
“…LAM cells produce proteolytic enzymes, which may contribute to lung cyst formation [8,9]. Matrix metalloproteinases (MMPs), can degrade extracellular matrix, and can affect cell growth, invasion, angiogenesis and inflammation [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chylothorax may be the first symptom of LAM, occurring as a primary manifestation in ~25% of patients (11,12). The obstruction of the lymphatic system is the most important mechanism underlying the establishment of chylothorax, while the obstruction of blood vessels leads to the formation of focal areas of hemorrhage and hemoptysis (13). The present study reported a sporadic case of LAM, in which the onset symptom was bloody sputum, and the diagnosis of LAM was confirmed 5 years after the initial presentation.…”
Section: Discussionmentioning
confidence: 99%